Taking lives [videorecording (DVD)] - Jolie, Angelina, 1975-; Hawke, Ethan, 1970-; Sutherland, Kiefer, 1966-; Pye, Michael, 1946- (Warner Home Video, 2004)
Illeana Scott is a special agent with the FBI, who has a strong record as a criminal profiler. Scott is called in by a former Quantico colleague to assist two Canadian police detectives, Paquette and Duval, who are on the trail of a serial killer who has been killing in and around Montreal for almost two decades. Art gallery owner James Costa saw the killer during an assault, and now finds himself working as a decoy for Scott. As Scott and Costa follow the killer's trail, they find themselves becoming attracted to one another, which is not a comfort to Scott.